Money matters: structural problems with implementing the DVA - Smythe, Dee; Artz, Lillian (Agenda (Durban), 2005)
The Domestic Violence Act has been in operation in South Africa for over five years. Studies conducted during this time throw into stark contrast the divergence between well-intended legislative interventions, systemic implementation problems, and the complex social relationships into which this Act seeks to intrude. In this article we focus on two interrelated issues that arise out of this context: economic abuse and the withdrawal of criminal and civil domestic violence related matters by victims of domestic violence. The article focuses its analysis on the impact of women's structured dependency and adverse socio-economic contexts in precipitating economic abuse and the decisions of domestic violence victims to withdraw cases.